The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ieam.1849
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptual approach for assessing risks from chemical mixtures and other stressors to coastal ecosystem services

Abstract: Growth of human populations and increased human activity, particularly in coastal areas, increase pressure on coastal ecosystems and the ecosystem services (ES) they provide. As a means toward being able to assess the impact of multiple stressors on ES, in the present study we propose an 8‐step conceptual approach for assessing effects of chemical mixtures and other stressors on ES in coastal areas: step A, identify the relevant problems and policy aims; step B, identify temporal and spatial boundaries; step C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…Aided by answering other priority research questions identified in the current paper, developing fundamental understanding of the specific Mode of Action (MOAs) of these chemicals will help determine their combined effects. However, the data generated need to be supported within ecological risk assessment models that are able to accurately predict cumulative effects, including ecosystems services (Syberg et al 2017). Herein, future research at the intersections of ecological stoichiometry and toxicology (i.e., how nutrition can affect the toxicity of contaminants, how contaminants can influence nutrient dynamics, or how nutrients can influence toxins production) promises to support an understanding of interactive effects of anthropogenic contaminants and algal toxins in nutrientenriched systems (Conine and Frost 2016).…”
Section: Multiple Stressors and Mixturesmentioning
confidence: 99%
“…Aided by answering other priority research questions identified in the current paper, developing fundamental understanding of the specific Mode of Action (MOAs) of these chemicals will help determine their combined effects. However, the data generated need to be supported within ecological risk assessment models that are able to accurately predict cumulative effects, including ecosystems services (Syberg et al 2017). Herein, future research at the intersections of ecological stoichiometry and toxicology (i.e., how nutrition can affect the toxicity of contaminants, how contaminants can influence nutrient dynamics, or how nutrients can influence toxins production) promises to support an understanding of interactive effects of anthropogenic contaminants and algal toxins in nutrientenriched systems (Conine and Frost 2016).…”
Section: Multiple Stressors and Mixturesmentioning
confidence: 99%
“…However, I pointed out that this is also an ecosystem loss to humans in terms of food production because pesticides and fertilizers adversely affect spawning anadromous salmons in adjacent streams. Similarly in Costa Rica, the world's second largest producer of bananas, intensely farmed monocultures involving large applications of pesticides have resulted in significant transfers of pesticides and fertilizers into adjacent waterbodies, adversely affecting the resident biota (Syberg et al 2017).…”
Section: Referencesmentioning
confidence: 99%
“…Clearly, conflicts of interest will occur; for example, an alternative solution may result in adverse effects to 1 ecosystem service, whereas another may benefit when the alternative is chosen. Syberg et al provide a case study of conflicting ecosystem services, specifically banana plantations benefiting from applying pesticides to their crops (e.g., increased terrestrial food production), while pesticide runoff from those plantations affects downstream ecosystems (e.g., reduced aquatic food production).…”
Section: Improving Risk Assessment and Management In A Complex And Chmentioning
confidence: 99%
“…Some of them are new; others are well known but not generally adopted. Two additional articles resulting from the workshop, published in the journal Integrated Environmental Assessment and Management and cited herein, provide relevant case studies and additional supportive information [1][2].…”
Section: Etandc Focusmentioning
confidence: 99%
See 1 more Smart Citation